O uso do tempo para mulheres que são mães e trabalham remuneradamente - Pereira, Lívia Cristina (Universidade Federal de São Carlos, 2023)
Historically and culturally, the responsibility for home and family care has been attributed to women. The inclusion of women in the workplace has not meant the reduction of productive and reproductive tasks, resulting in overloaded routines and highlighting gender inequality in the division of labor. The present study seeks to understand how time is used by women who are mothers and engage in paid work. The study was carried out in a medium-sized city in the state of São Paulo, and it is descriptive research with a qualitative approach, in which three women were interviewed, mothers of one or more children, aged between 0 (zero) and 10 (ten) years, who have formal or informal full-time paid work. The data production was done through semi-structured interviews, and the analysis and discussion of the data obtained was done by thematic analysis. The results showed the importance of a support network, the female responsibility for housework, and the role of leisure activities and self-care for the maintenance of well-being. The impact of the pandemic was also examined. With this, it is possible to conclude that the relationship between personal time and maternity time still has extreme social relevance. Professionals and services offered to this group must consider the use of time and its social conditioning factors, so that the overload still existing in women's participation in society is not made invisible. It is hoped that this study will contribute to the practices of occupational therapy professionals while working with this population.
The use of time for women who are mothers and work for pay
Keywords: Uso do Tempo; Mulheres; Mães; Trabalho; Time use; Women; Mothers; Work; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA